Brain neuroreceptor density and personality traits: towards dimensional biomarkers for psychiatric disorders. (19th April 2018) - Farde, Lars; Plavén-Sigray, Pontus; Borg, Jacqueline; Cervenka, Simon
Abstract : Positron emission tomography has, for 30 years, been used in numerous case-control studies searching for hypothesized differences in the density of neuroreceptor or transporter proteins in psychiatric disorders such as schizophrenia and depression. In most cases, the results have not been conclusive. One reason could be the sizeable interindividual variability in biochemical markers, which in twin studies have shown to emanate from both environmental and genetic factors, leading to low statistical power for the detection of group effects. On the other hand, the same interindividual variability has served as an opportunity for correlative studies on the biological underpinning of behaviour. Using this approach, a series of studies has linked markers for the dopamine and serotonin system to personality traits associated with psychiatric conditions. Based on increasing evidence for the view that many psychopathological states represent extremes of a continuum rather than distinct categories, this research strategy may lead to new biological insights about the vulnerability to and pathophysiology of major psychiatric disorders. This article is part of the theme issue 'Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences'.